Data from: MHC variability in an isolated wolf population in Italy - Galaverni, Marco; Caniglia, Romolo; Fabbri, Elena; Lapalombella, Silvana; Randi, Ettore (Zenodo, 2013)
Small, isolated populations may experience increased extinction risk due to reduced genetic variability at important functional genes, thus decreasing the population's adaptive potential. The major histocompatibility complex (MHC), a key immunological gene cluster, usually shows high variability maintained by positive or balancing selection in response to challenges by pathogens. Here we investigated for the first time, the variability of 3 MHC class II genes (DRB1, DQA1, and DQB1) in 94 samples collected from Italian wolves. The Italian wolf population has been long isolated south of the Alps and is presently recovering from a recent bottleneck that decreased the population to less than 100 individuals. Despite the bottleneck, Italian wolves show remarkable MHC variability with 6–9 alleles per locus, including 2 recently described alleles at DRB1. MHC sequences show signatures of historical selective pressures (high d N/d S ratio, ω > 1.74) but no evidence of ongoing selection. Variation at the MHC genes and 12 background microsatellite loci were not apparently affected by the recent bottleneck. Although MHC alleles of domestic dog origin were detected in 8 genetically admixed individuals, these alleles were rare or absent in nonadmixed wolves. Thus, despite known hybridization events between domestic dogs and Italian wolves, the Italian wolf population does not appear affected by deep introgression of domestic dog MHC alleles. MHC alleles and STR genotypes of wolves in Italy Galaverni_et_al_2013_STR_MHC.xlsx